Resiliensi Akademik Mahasiswa Tingkat Akhir Program Studi Bimbingan dan Konseling Tahun Ajaran 2021/2022 - Clareta Thesalonika Okvellia; Anastasia Setyandari (Program Studi Bimbingan dan Konseling, Universitas Sanata Dharma, 2022)
Problems in academic life can make students become stressed until they decide to stop studying. Academic resilience is an individual's ability to persist in completing their education even under challenging conditions or unpleasant situations and solve an academic problem. The purpose of this study was to describe the academic resilience of final year students, Guidance and Counseling Study Program of Sanata Dharma University, Academic Year 2021/2022. The result showed that the academic resilience of final year students for the academic year 2021/2022 was in the high category with a percentage of 64,7%. Based on the items with low scores on the questionnaire, the researcher proposed several topics to improve academic resilience of the students.